Reaksi Pasar Modal Atas Kenaikan The Federal Funds Rate Pada Tanggal 26 September 2018 - Indrayuda, Anak Agung Gede Agung; Sukartha, I Made (E-Jurnal Akuntansi; Vol 29 No 2 (2019)DO - 10.24843/EJA.2019.v29.i02.p27, 2019)
In the modern economic system, the role of the capital market is very important as a place where emiten and investors meet. Internal information and external information are needed by investors as a basis for consideration in investment decision making. By looking at the presence or absence of average abnormal returns and average trading volume activity around the event period, this study aims to examine the market reaction to the Federal Funds Rate increase on September 26, 2018. LQ45 is a stock index used as a sample in this study using a purposive sampling technique as a method in sample selection. This study uses one sample t-test, paired sample t-test, and Wilcoxon signed rank test as data analysis techniques. The finding of the significance of average trading volume activity around the event period indicates that the market reacted to the FFR increase on September 26, 2018. However, the results of the study showed no significance of average abnormal return around the event period. Keywords: event study, abnormal return, trading volume activity. Keywords : Event Study; Abnormal Return; Trading Volume Activity.